Integrative Approach in Haemophillic Arthropathy of The Knee: a Case Report - Andri Maruli T Lubis; Kurniadi Husodo; Lugyanti Sukrisman; Djajadiman Gatot (Acta Medica Indonesiana, 2016)
Haemophilic arthropathy is the most prevalent joint disorder in haemophilia. This disorder is characterized by chronic synovitis and progressive destruction of joint cartilage. We report a case of arthroscopic synovectomy to reduce bleeding frequency in haemophilic arthropathy of the knee. Patient was a 15 years old male with haemophilic arthropathy of the left knee. We performed an arthroscopic synovectomy under tightly regulated factor VIII replacement therapy. There were villous synovial hypertrophy at all part of the joint, multiple bone and cartilage defect, and also anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL) deficiency found intraoperatively. After 6 month follow up, subjective complain and bleeding frequency decreased significantly. The visual analog scale improved from 5-6 to 1-2, and the International Knee Documentation Committee Score increased from 49 to 66. Bleeding frequency decreased from 4-8 times per month to less than 1 time per month. Arthroscopic synovectomy performed in this case could reduce the pain, decrease the frequency of bleeding, and improve patient’s functional outcome.